Entre la flecha y el altar: el adoctrinamiento femenino del franquismo. Valladolid como modelo, 1939-1959 - Gómez Cuesta, Cristina (Cuadernos de Historia Contemporánea, 2009)
This article explores the existing differences and similarities between the two organizations in charge of the indoctrination of women in Spain after the Civil War: the Feminine Section of FET-JONS and the feminine branch of Catholic Action. The study will firstly approach the ideology of new femininity imposed by the Francoist regime and executed by the two organizations, secondly, their more outstanding actions related to education and social assistance, and finally the existing contradictions in their discourse according to the activism of their commands and the submission to the regime’s dictates. The chosen spatial framework is the city of Valladolid, being an ideological benchmark and model of adhesion where the mechanism of socialization and national regeneration planned by the New State can be applied.